Directions : Hirshhorn Museum and Sculpture Garden - Fox, Howard N.; Hirshhorn Museum and Sculpture Garden, Washington (Washington : Smithsonian Institution, 1979)
Kuehn, George ; Madsen, Loren ; Van Alstine, John ; Kessler, Alan ; Nelson, Jud ; Saari, Peter ; Hudson, Robert ; MacConnel, Kim ; Rossi, Barbara ; Schirm, David ; Antin, Eleanor ; Attie, Dotty ; etc.
Directions, Hirshhorn Museum and Sculpture Garden, Washington, June 14 - September 3, 1979
Engels
kunstcatalogus